Rapid, Selective and Rugged LCMS/MS Method Development and Validation for the Estimation of Clarithromycin in Dog Plasma. Issue 2 (3rd March 2016) - Malladi, Madhusudhan; Jukanti, Raju
Abstract: A new, simple, fast, sensitive and selective high performance liquid chromatography (HPLC) coupled with electrospray ionization tandem mass spectrometric method (LC-MS/MS) was developed and validated for the determination of clarithromycin in beagle dog plasma using imipramine as internal standard. The analyte was chromatographed under isocratic conditions on inertsil ODS 3 V (250X4.6 mm) 5μ column using mobile phase of 0.1% Formic acid: Methanol (15:85% v/v). The column temperature and flow rate was 40 ± 5°C and 1 ml/min respectively. The retention time for clarithromycin is within 1.52 min. Analysis was performed in the negative ionization mode using multiple reaction monitoring of the ion transitions at m/z 748.37/157.83 for clarithromycin and m/z 280.98/85.94 for internal standard, respectively. The validation was carried out over 9.922 - 4037.459 ng/ml of clarithromycin with the correlation coefficient of ≥ 0.9950. Method was validated for linearity, precision, accuracy, specificity, sensitivity, matrix effect, dilution integrity, ruggedness, reinjection reproducibility and stability. Clarithromycin was stable in stock solutions and in dog plasma samples under representative storage conditions. The present developed and validated method could be useful for the estimation of clarithromycin in beagle dog plasma.